Fasting in Countries Where The Day is Very Long or Very Short: A Study of Muslims in the Netherlands - Burhani, Ahmad Najib (Al-Jamiah: Journal of Islamic Studies, 2013)
Ramadan falls both during winter and autumn months, when the days are cool and short, and spring and summer months, when the days are long and hot. Fasting in areas where the climate is extremely hot and the day is more than twenty hours is a double hardship that can be a dangerous assault on physical condition. In contrast to that, fasting in areas where the day is very short is, to some extent, like an interval between breakfast and lunch or between lunch and dinner. This article, therefore, intends to discover how Muslims in the countries where the day is either very long or very short deal with the problem of the fasting time. This research is based on the practices of some Muslims in the Netherlands with a variety of countries of origin. This article attempts to answer the following questions: How did they manage their fasting time in the summer or when the day is very long? How did they manage their fasting time in the winter or when the day is very short? What kind of fiqh book or fatwÄ did they use as reference? Did they think that fasting obligation was dangerous for their health when the day was very long?[Bulan Ramadan bisa tiba pada musim dingin dan musim gugur, ketika siang hari pendek dan sejuk, tetapi Ramadan juga bisa tiba pada musim semi dan musim panas, ketika siang hari sangat panjang dan panas. Puasa di tempat yang sangat panas dan dengan panjang siang hari lebih dari dua puluh jam adalah beban yang berat dan bisa berbahaya bagi kondisi fisik pelakunya. Sebaliknya, puasa di tempat yang siang harinya sangat pendek terasa tak seperti puasa karena ia hanya seperti interval antara makan pagi dan makan siang atau antara makan siang dan makan malam. Tulisan ini didasarkan pada penelitian terhadap praktik berpuasa orang-orang Islam di Belanda dari berbagai negara asal. Pertanyaan yang ingin dijawab dalam tulisan ini adalah: Bagaimana umat Islam Belanda melaksanakan puasa pada musim panas atau ketika siang hari teramat panjang? Bagaimana pula mereka menjalankan puasa pada musim gugur atau ketika siang hari sangat pendek? Buku fikih apa atau fatwa dari siapa yang mereka pakai sebagai dasar praktik ibadah puasa itu? Apakah mereka berpikir bahwa praktik puasa di musim yang siang harinya sangat panjang akan berbahaya bagi kesehatan mereka?